التمثلات الأخلاقية في الحضارة الإسلامية "دراسة تحليليّة لآراء المستشرق مارشال هود جسون في كتابه مغامرة الإسلام" (Journal of Imam Al-Kadhim College, 2023)
Islamic civilization has many aspects and diverse drinks, in which morality occupies an important and large aspect of it because it stems from the human being as its engine, as morals represent the spiritual dimension and the true essence on which states are based in their emergence and their development through historical eras, and at the same time they are the secret of their survival and immortality throughout the history of generations. Naturally, if this aspect is engulfed, the aspects of civilization are warned of danger or demise, and we do not exaggerate if we say that the morals and values ​​witnessed by Islamic civilization have surpassed their counterparts in other civilizations, thanks to Islam, the tolerant Sharia, and what it recommended in adopting those noble values, and therefore It became a matter of interest to Westerners, including the Orientalists, so they began embodying it in their books and writings.On the other hand: The orientalists have scrutinizing and critical opinions on the process and life of civilizations that differed according to different orientations, ideas, and data.The first is to introduce the author, Marshall Hood Jason, and the author, The Adventure of Islam, as one of the recent books in the arena of Arab culture. It was not printed until 2021 AD, and it is a virgin in the field of Islamic studies.As for the second axis, it began presenting the views of the orientalists about civilizations, and the field of their survival or their demise, each according to his orientation, and his opinion until the place ended for the third axis, which deals with the new idea put forward by Hood Jason, which is the moral dimension of Islamic civilization. The positive vision of Islamic civilization.
Keywords: كلمات مفتاحية : استشراق-حضارة –اخلاق-مارشال هودجسون